2011
DOI: 10.1111/j.1532-5415.2011.03703.x
|View full text |Cite
|
Sign up to set email alerts
|

Coprophagia and Pica in Individuals with Mild to Moderate Dementia and Mixed (Iron Deficiency and Macrocytic) Anemia

Abstract: disorder clinic were reviewed. All participants underwent brain magnetic resonance imaging to augment diagnostic accuracy. For the same reason, metaiodobenzylguanidine (MIBG) cardiac scintigraphy was performed in most participants. Individuals with a history of abdominal surgery, gastrointestinal diseases such as ulcerative colitis and cholecystolithiasis, diabetes mellitus, and other systemic diseases that might potentially cause IPO or volvulus were excluded. For the same reason, individuals patients taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…In some patients, imaging studies reported cerebral atrophy, particularly of the medial temporal lobe [1]. As found in our case series, the laboratory findings were diverse [24]. We also explored psychological symptoms which were also noted to be diverse.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…In some patients, imaging studies reported cerebral atrophy, particularly of the medial temporal lobe [1]. As found in our case series, the laboratory findings were diverse [24]. We also explored psychological symptoms which were also noted to be diverse.…”
Section: Discussionmentioning
confidence: 71%
“…The two patients discussed in this report present with symptoms of coprophagia in the context of an acute exacerbation of chronic psychiatric disorders. In prior case reports in the literature, the disorders often associated with coprophagia were cognitive disorders [1, 2] and schizophrenia spectrum disorders [4, 5]. Of note, these patients presented with affective spectrum disorders (bipolar disorder).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Organic brain causes, like amygdala damage, were ruled out by the request of an MRI. Additionally, he did not present any vitamin deficiencies or any blood count disturbances, particularly iron deficiency or macrocytic anemia, which could be an etiologic factor as pointed out by Sharma et al [ 7 ].…”
Section: Discussionmentioning
confidence: 84%